IntraVoxel Incoherent Motion (IVIM) MRI of fetal lung and kidney: Can the perfusion fraction be a marker of normal pulmonary and renal maturation?. Issue 139 (June 2021) - Ercolani, Giada; Capuani, Silvia; Antonelli, Amanda; Camilli, Arianna; Ciulla, Sandra; Petrillo, Roberta; Satta, Serena; Grimm, Robert; Giancotti, Antonella; Ricci, Paolo; Catalano, Carlo; Manganaro, Lucia
Highlights: Perfusion fraction f significantly increases with GA in both fetal lung and kidney. f mean values are significantly higher in older fetuses than youngers. IVIM parameter f as a potential marker of fetal lungs and kidneys maturation. IVIM can detect microstructural tissue changes occurring in fetal lungs and kidneys. Abstract: Purpose: To investigate the use of IntraVoxel Incoherent Motion (IVIM) MRI in the study of microstructural tissue changes occurring in fetal lung and kidney during gestation. Methods: 34 normal pregnancies were enrolled. Patients were divided into two groups based on gestational age (GA): group A (21−29 weeks) and group B (30−39 weeks). MR examinations were performed at 1.5T, with a standard fetal MR protocol including a Diffusion-Weighted Echo-Planar Imaging sequence with 10 different b-values (0, 10, 30, 50, 75, 100, 200, 400, 700, 1000s/mm 2 ). For each fetus, two bilateral ROIs were manually placed in lung and renal parenchyma. Mean values of perfusion fraction f, pseudo-diffusion coefficient D* and diffusion coefficient D were obtained. The correlation between IVIM parameters and GA was investigated. Results: In renal ROIs a positive correlation between fkidney and GA (p < 0.005) was found; similarly flung showed a statistically significant correlation with GA (p < 0.001). F mean values were significantly higher in group B compared to group A in both renal (p = 0.0002) and lung (p = 0.018) ROIs. No correlation was found in D and D* as a function of GA. Conclusions: The IVIM perfusion fraction f may be considered as a potential marker of pulmonary and renal maturation in relation to hemodynamic changes described in intrauterine life. Our results highlight that IVIM model is useful as an additional prenatal diagnostic tool to study lung and renal development.